Laserterapia no tratamento da síndrome genitourinária da menopausa: revisão sistemática e metanálise de ensaios clínicos randomizados - Nóbrega, Lisieux de Lourdes Martins (2023)
Laser therapy has been proposed to improve the symptoms of genitourinary syndrome of menopause (GSM), especially in women who do not accept or have a high risk of complications if they undergo hormonal therapy. However, studies evaluating the efficacy and safety of laser treatment for GSM have shown controversial results. Therefore, the objective of the study is to evaluate the effects of laser therapy in menopausal patients with GSM. A systematic review and meta-analysis of randomized clinical trials (RCTs) was carried out based on a protocol published in a scientific journal, prospectively registered through the International Prospective Register of Systematic Reviews (PROSPERO/CRD42021253605) and following the Preferred Reporting Items for Systematic Review and Meta-analysis Protocol, using the PICOS strategy to find studies with postmenopausal women without treatment, or undergoing laser therapy, placebo, or vaginal estrogen for GSM. According to the protocol, randomized and quasi-randomized clinical trials, regardless of the language of publication, were searched in databases using keywords, and the results were systematically evaluated for vaginal atrophy, pH, dryness, dyspareunia, itching, burning, dysuria, frequency, urgency, and urinary incontinence. The results of the review provided evidence that carbon dioxide (CO2) laser increases the Vaginal Health Index (VHI) score and decreases dyspareunia, dryness, and burning, especially when compared to placebo, but with low certainty of evidence.